PERAN PEMERINTAH DAERAH DALAM PERLINDUNGAN HAK ANAK MELALUI PEMBENTUKAN KABUPATEN/KOTA LAYAK ANAK (KRA) - Roza Dahlia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Protection and empowerment and supervision of children's rights are shared responsibilities. However, in this case, the State/Government through the legal umbrella guarantees the implementation of the protection, maintenance and welfare of children by taking into account the rights and obligations of parents, guardians or other people who are legally responsible for children. The state and government guarantee children to get their rights as contained in the Child Protection Act. Of course, in synergy with the local government, community and parents. Regions as an extension of the center Regional governments play a very important role in protecting children's rights, one of which is the local government in empowering children's rights by making governor/provincial/city regulations regarding the implementation of child protection. /Child-friendly cities and the establishment of regional institutions that support the protection and empowerment of children's rights, especially those in the regions.Keywords: Protection, Government, Protecting Children's Rights.